PENGARUH MODEL DIRECT INTERACTION BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPA MATERI ORGAN GERAK HEWAN - Ruri Wahyuningsih; Ricka Tesi Muskania (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the direct interaction model assisted by puzzle media on student learning outcomes in Natural Science (IPA) learning on animal locomotory organs. The background of this study is based on the low learning outcomes of students in the subject of Natural Science, especially on the material of animal locomotory organs. The approach used in this study is a quantitative approach with an experimental research type. The research design used is One group pretest-post-test design. Sampling was carried out using a purposive sampling technique. Student learning outcomes in science learning on animal locomotory organs for grade V at SDN 4 Batu Ampar District in the 2022- 2023 academic year applying direct interaction assisted by puzzle media have learning outcomes of 29 students on the pre-test questions 34.51 while the post-test 71.006 from the numbers can be described as an increase in learning outcomes after applying the direct interaction model assisted by puzzle mediaKeywords.